2018
DOI: 10.1038/s41593-018-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic tau-induced piRNA depletion promotes neuronal death through transposable element dysregulation in neurodegenerative tauopathies

Abstract: Transposable elements, known colloquially as 'jumping genes', constitute approximately 45% of the human genome. Cells utilize epigenetic defenses to limit transposable element jumping, including formation of silencing heterochromatin and generation of piwi-interacting RNAs (piRNAs), small RNAs that facilitate clearance of transposable element transcripts. Here we utilize Drosophila melanogaster and postmortem human brain samples to identify transposable element dysregulation as a key mediator of neuronal death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
275
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(305 citation statements)
references
References 67 publications
28
275
1
1
Order By: Relevance
“…Prior studies have profiled brain gene expression in Tau transgenic animals, including in flies [31,32,52] and mouse models [21,23,41]; however, none to our knowledge have longitudinally assessed both transcripts and proteins in parallel. Our analyses provide a glimpse of the dynamic regulatory crosstalk between the brain transcriptome and proteome that respond to brain injury, as in tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have profiled brain gene expression in Tau transgenic animals, including in flies [31,32,52] and mouse models [21,23,41]; however, none to our knowledge have longitudinally assessed both transcripts and proteins in parallel. Our analyses provide a glimpse of the dynamic regulatory crosstalk between the brain transcriptome and proteome that respond to brain injury, as in tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown that expressed retrotransposon RNAs can also be toxic through aberrant recognition by innate immune components in Aicardi-Goutieres Syndrome (Crow and Manel, 2015). Other studies linked transposon activation in Alzheimer's disease with tau aggregation, and suggest these alterations accompany neuroinflammation and genomic instability (Guo et al, 2018;Sun et al, 2018). DNA damage and structural variants induced by transposition itself are a formal possibility, given the elevated levels of the fully competent LINE-1Hs retrotransposon, and evidence for active L1Hs transposition in human neurons (Evrony et al, 2016;Upton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…neurons has been proposed to contribute to age-dependent 337 neuronal decline in wildtype and disease models of Drosophila and (Li, e al., 2013; Guo et 338 al., 2018;Sun et al, 2018). Although the frequency of neural transposition is debated,339 expression is a prerequisite for movement.…”
mentioning
confidence: 99%